Artifacts in electrocardiogram interpreted as cardiac arrhythmias: Reports of clinical cases - AL-HAMDI, AMAR Talib (Journal of the Faculty of Medicine Baghdad, 2021)
Background: Artifact waves in the ECG and Holter recording are not rare in clinical practice and can be mistaken for tachyarrhythmia.Objective: To orient the practicing physicians to differentiate these artifacts from cardiac arrhythmias.Patients and Methods: Thirteen patients with incorrectly diagnosed cardiac arrhythmias by ECG or Holter recording then distinguished to be ECG artifacts were included in this study. The patients were collected from the author’s private practice in the northern Iraqi governorate of Sulaimanya during the period from June 2015 to August 2020. The differentiation of the artifact waves from the arrhythmias were made by careful inspection of the ECG, identification of the R waves within the artifact waves and correlating the artifact waves with the patient’s symptoms.Results: The artifacts were mistaken for ventricular fibrillation in two patients, ventricular tachycardia in four, atrial fibrillation in two, atrial flutter in four, and in one patient bradycardia of high grade atrio-ventricular block.Conclusion: Distinguishing artifact in ECG and differentiating them from cardiac arrhythmia is important to avoid mismanagement.